Screening for thalassaemia in pregnant women: a laboratory perspective - George, Elizabeth; Khoo, S. K.; Abu Bakar, Mokhtar; Umar, Nor Aini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Aim: To investigate whether in Malaysia, a mean corpuscular volume (MCV) less than 80 f1 and mean corpuscular haemoglobin (MCH) less than 27 pg will identify carriers in pregnant women with severe forms of thalassaemia, α-thal 1 (α°) and classical β (β°)- thalassaemia. The results from this study will aid the implementation of a national program to screen for thalassaemia. Methods: For classical β (β°)- thalassaemia, blood samples collected in EDTA from 153 pregnant women were taken for full blood counts and haemoglobin subtyping by automated blood counting and high performance liquid chromatography (HPLC) respectively. For α-thal 1 (α°), the full blood counts were obtained from archives of 30 pregnant women who were genotyped positive for the α-thal 1 (α°) during prenatal diagnosis for Hb Barts hydrops fetalis. The effects of storage on MCV, MCH and Hb A₂ were determined by tests done daily for 3 weeks. Results: By correlating red cell indices with high performance liquid chromatography and genotypes data, we show that mean corpuscular volume (MCV) <80f1 and mean corpuscular haemoglobin <27pg is able to detect all heterozygous carriers with classical β (β°)- thalassaemia. On storage, MCV of heterozygous carriers with classical β (β°)- thalassaemia rose at 1% a day after 24 hours reaching a mean of 80 f1 by day 15. However, the MCH and Hb A₂ were stable for 3 weeks. Conclusion: A mean corpuscular haemoglobin <27pg should be recommended as cut-off values for screening of carries of α-thal 1 (α°) and classical β (β°)- thalassaemia. In blood samples, not processed within a day, MCH with a cut-off 27pg is the recommended choice for screening of carriers.